Storybridge to second language literacy : the theory, research, and practice of teaching English with children's literature - Ghosn, Irma-Kaarina (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
Storybridge to Second Language Literacy makes a case for using authentic children's literature--alternately also referred to as 'stories' or 'real books'--as the medium of instruction in teaching English to young learners, particularly in contexts where children must access general curriculum subjects in English. The author first proposes theoretical foundations for the argument that illustrated children's books are superior to traditional language teaching courses in the primary school. She builds the case around the motivational power of stories, the language and content of quality children's literature, and the potential of literature to contribute to development of second language academic literacy. She then reviews research of the past thirty years that clearly supports her claim. Finally, she uses transcripts from real classrooms to illustrate how teachers in diverse contexts make use of stories. Through the classroom vignettes, a practical model of literature-based instruction emerges that is adaptable to a wide range of primary school teaching contexts, including English as a second language contexts in core-English countries.Storybridge to Second Language Literacy compiles in one volume solid theoretical foundations for story-based instruction, research evidence of the past thirty years supporting the approach (not currently available in a single source), and extensive classroom vignettes illustrating diverse practical applications (not lesson plans).This makes the book valuable for anyone in the field of young learner ELT.MA students in TESOL will find the book useful and will develop an understanding of why and how literature-based instruction works and develop insight to guide their practice. Members of TESOL Elementary Education, EFL, and Bilingual Education SIGs, and IATEFL Young Learner SIG will be interested in the volume. Instructors of teacher development courses should also find the proposed volume a valuable addition to assigned readings. Each chapter is followed by 'Think about it' questions and 'Try it out' suggestions.